Ancient Oral Tradition Describes Volcano–Earthquake Interaction at Merapi Volcano, Indonesia. Issue 1 (March 2015) - Troll, Valentin R.; Deegan, Frances M.; Jolis, Ester M.; Budd, David A.; Dahren, Börje; Schwarzkopf, Lothar M.
Abstract Merapi volcano is among the most hazardous volcanoes on the planet. Ancient Javanese folklore describes Merapi's activity as the interaction between the Spirit Kings that inhabit the volcano and the Queen of the South Sea, who resides at Parangtritis beach, 50 km SSE of Merapi. The royal palace in Yogyakarta is located half‐way along the hypothetical line between Merapi and Parangtritis (the Merapi–Kraton–South Sea axis) to bring balance between these mystical forces. In 2006 and 2010, Merapi erupted explosively and on both occasions, earthquakes shook the region and the eruptions grew more violent in response. These earthquakes appear to influence the sub‐volcanic magma supply of Merapi and a positive feedback loop has recently been postulated between the volcano and local earthquake patterns. The 2006 earthquakes clustered along the Opak River fault to the south of the volcano, which trends NE–SW, and reaches the southern sea at Parangtritis beach, the fabled residence of the Queen of the South Sea. Our interpretation of the Merapi–Kraton–South Sea axis is that local folklore was used by ancient people to describe and rationalize the complex interplay between geological processes. We suggest that Merapi displayed volcano–earthquake interaction many times in the past, and not only during its most recent eruptive cycle. Although now shrouded in mystery, these oral traditions can be thought of as an ancient hazard mitigation tool, which makes them likely useful in helping to foster effective dialogues with a variety of target parties and interest groups around the volcano's slopes.